DRAVET ENGAGE. Parent caregivers of children with Dravet Syndrome: Perspectives, needs, and opportunities for clinical research - Juandó-Prats, Clara; James, Emma; Bilder, Deborah A.; McNair, Lindsay; Kenneally, Noah; Helfer, Jennifer; Huang, Norman; Vila, Maria Candida; Sullivan, Joseph; Wirrell, Elaine; Rico, Salvador (My University, 2021)
Dravet syndrome (DS) is an intractable developmental and epileptic encephalopathy significantly impacting affected children and their families. A novel, one-time, adeno-associated virus (AAV)-mediated gene regulation therapy was designed to treat the underlying cause of DS, potentially improving the full spectrum of DS manifestations. To ensure the first-in-human clinical trial addresses meaningful outcomes for patients and families, we examined their perspectives, priorities, goals, and desired outcomes in the design phase through a mixed methods approach (quantitative and qualitative). We conducted a non-identifiable parent caregiver survey, shared through a patient advocacy organization (n = 36 parents; children age 6 years). Parents were also engaged via three group discussions (n = 10; children age 2– 20 years) and optional follow-up in-depth individual interviews (n = 6). Qualitative data analysis followed an inductive interpretive process, and qualitative researchers conducted a thematic analysis with a narrative approach. Survey results revealed most children (94%) were diagnosed by age 1, with onset of seizures at mean age 6.2 months and other DS manifestations before 2 years. The most desired disease aspects to address with potential new disease-modifying therapies were severe seizures (ranked by 92% of caregivers) and communication issues (development, expressive, receptive; 72–83%). Qualitative results showed the need for trial outcomes that recognize the impact of DS on the whole family. Parents eventually hope for trials including children of all ages and were both excited about the potential positive impact of a one-time disease-modifying therapy and mindful of potential long-term implications. Participants reflected on the details and risks of a clinical trial design (e.g., sham procedures) and described the different factors that relate to their decision to participate in a trial. Their main aspirations were to stop neurodevelopmental stagnation, to reduce seizures, and to reduce the impact on their families’ wellbeing. To our knowledge, this is the first study within a patient-oriented research framework that specifically explored parents’ needs and perceptions regarding clinical trials of a potential disease-modifying therapy for children with a severe, developmental disease, such as DS.
Keywords: Dravet syndrome; caregiver perspectives; clinical trial; gene therapy; patient and caregiver engagement